Rare association of multiple etiologies in a severe oligoasthenospermic male - V.S., Vineeth; Najafi, Mohsen; G., Sreenivasa; Kumar C., Sharath; Malini, Suttur S. (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>We report a rare case of a 30 year old man diagnosed with severe oligoasthenospermia, where the infertile condition is traced back to a multiple etiologies. Routine semen analysis and sperm function tests followed by hormone analysis are carried out to diagnose the condition as well as the severity. The initial findings prompt us to perform Ultrasound scanning of testis and Trans Rectal Ultrasound Scanning (TRUS) to check the anatomical and functional status of the accessory reproductive organs. Semen analysis and sperm function tests provide an insight into the severity of the condition. The hormonal analysis, Ultrasound scanning of testis and TRUS of accessory reproductive glands confirms the association of hormonal imbalance, testis and accessory gland defects which results in the observed infertile condition with severe sperm defects. A thorough investigation of infertile subjects is essential for appropriate diagnosis and effective personalized treatment owing to the probability of multiple etiologies. Incomplete diagnosis can have adverse effects in treatment and Assisted Reproductive Techniques (ART).